Integration of UNCAC Anti-Corruption Standards In The Supervision of Private Corporations In Indonesia - Muh. Syarif Lamanasa; Suardi Rais; Jupri (Cattleya Darmaya Fortuna, 2025)
Private sector corruption has become a critical challenge alongside the growing role of corporations in national economic development. Although Indonesia has ratified the United Nations Convention against Corruption (UNCAC), the integration of its anti-corruption standards into the supervision of private corporations remains inadequate. This study examines the extent to which UNCAC standards have been incorporated into Indonesia’s national legal framework, particularly in relation to preventive supervision of private corporations, and assesses their effectiveness in addressing private sector corruption. Employing a normative legal research method supported by statutory, conceptual, and limited comparative approaches, this study analyzes international and national legal instruments governing corporate supervision and anti-corruption measures. The findings indicate that Indonesia’s regulatory framework remains predominantly focused on criminalization and punitive enforcement, while preventive mechanisms such as mandatory corporate compliance, beneficial ownership transparency, and inter-agency supervisory coordination are insufficiently regulated and weakly implemented. This study argues that strengthening the integration of UNCAC standards through a supervision-based and preventive approach is essential to enhancing corporate integrity, improving the business climate, and supporting sustainable economic development in Indonesia.